Makna Benbepon dalam Tradisi Ararem sebagai Strategi Budaya Masuknya Masyarakat China di Pulau Biak, Papua: Kajian Antropolinguistik - Kandam, Clementina Vincencia; Ardhian, Dany (Universitas Lampung, 2025)
The existence of benbepon according to stories circulating for generations began with Chinese traders who came to eastern Indonesia, especially on Biak Island, Papua. History proves that before the 15th century, Papuans had already established relationships with foreign nations such as traders from China, Spain and Potrugal. On the way back to their hometowns, it was not uncommon for Biak people to meet Chinese traders who wanted to go to the same destination. But before passing through or stopping to settle on Biak Island, the Biak tribe community, has a request that must be fulfilled, namely they must leave something in the form of goods or objects as a condition that they are accepted by the Biak tribe community. Then foreign ceramic objects such as plates and jars were given by Chinese Chinese traders to the Biak tribal community. Biak people call these foreign ceramic objects “Benbepon”. The research method used is linguistic anthropology which aims to examine language with a cultural, social context in the naming of benbepon motifs in the ararem tradition of the Biak tribe. then the data is analyzed using Barthes' semiotic theory, namely denotative and connotative meanings to find out and describe the symbolic meaning and form of benbepon motifs and shapes. Based on the results and discussion of the History of Chinese Arrival. benbepon is classified by the Biak tribe based on age, motif, shape and sound. The results of the classification are ten types of benbepon, but in the Biak tribe's ararem tradition which is used until now only 8 types of benbepon such as the embossed dragon snake motif (Benkorben), koi/gold fish (Benkarip), roses (Paramasi/Resa-resa Paramasi), paradise occupying tifa, to the honai house (Benayemer). Then the benbepon motif has a symbolic meaning in the ararem tradition for the Biak tribe, which symbolizes prosperity, protection, luck, fertility, peace, and self-identity that must be preserved. Benbepon also has anthropological aspects in the ararem tradition, namely the acculturation process in the benbepon and the function of benbepon in Biak society. Keywords: Benbepon,Ararem Tradition,Chinese Traders